78.5k views
1 vote
CAN SOMEONE PLEASE HELP ME SOLVE THIS?!!!! find k
(g)/(\:e)-(x)/(k)-(1)/(b)=y

2 Answers

3 votes

\bf \cfrac{g}{e}-\cfrac{x}{k}-\cfrac{1}{b}=y\impliedby \begin{array}{llll} \textit{let's multiply both sides by }\stackrel{LCD}{ekb}\\ \textit{to do away with the denominators} \end{array} \\\\\\ ekb\left( \cfrac{g}{e}-\cfrac{x}{k}-\cfrac{1}{b} \right)=ekb(y)\implies kbg-ebx-ek=ekby \\\\\\ kbg-ebx-ek-ekby=0\implies kbg-ek-ekby=ebx \\\\\\ k(bg-e-eby)=ebx\implies k=\cfrac{ebx}{bg-e-eby}
User Allquixotic
by
4.8k points
3 votes
The LCD is c*k*b. Mult. all 4 terms by this LCD:

g*k*b - x*c*b - c*k = y*c*k*b

Find k. To do this, factor the left side, obtaining k(g*b - c) = y*c*k*b

Then divide both sides by (g*b-c).
User Dasony
by
5.8k points